E-Court dan Akses Keadilan Digital: Kajian Sosiologi Hukum terhadap Perubahan Pelayanan Peradilan - Mariatul Kiptiah; Fachruji Fachruji; Muhammad Aini (AHKAM, 2026)
Although digital transformation in the judicial system has been widely studied, research that specifically discusses the implementation of E-Court from the perspective of the sociology of law and its implications for access to digital justice remains limited. This study aims to analyze the implementation of E-Court and its influence on access to digital justice, the transformation of legal culture, and patterns of social interaction in judicial services in Indonesia. This study used a qualitative approach with a case study design involving judges, court clerks, advocates, and members of the public who use E-Court services. Informants were selected through purposive sampling based on their direct involvement in the use of electronic judicial services. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that the implementation of E-Court has transformed the judicial service system through improved administrative efficiency, transparency, and accessibility of court services. However, digital inequality, low technological literacy, and limited infrastructure remain major obstacles to equitable access to digital justice. In addition, the shift from conventional judicial services to a digital system has also affected patterns of social interaction and the legal culture of justice seekers. These findings contribute to the development of studies in the sociology of law, particularly regarding the relationship between law, technology, and social change in the digital era. The conclusion of the study affirms that the implementation of E-Court serves not only as an administrative innovation but also as an instrument for transforming legal culture and expanding access to digital justice. The implications of this study provide practical contributions for the Supreme Court of the Republic of Indonesia and relevant stakeholders in strengthening digital literacy, technological infrastructure, and judicial policies that are more inclusive and responsive to public needs.